A novel major facilitator superfamily-type tripartite efflux system CprABC mediates resistance to polymyxins in Chryseobacterium sp. PL22-22A - Zhang, Lu; Wang, Miao; Qi, Rui; Yang, Yilin; Liu, Ya; Ren, Nianqing; Feng, Zihan; Liu, Qihao; Cao, Guangxiang; Zong, Gongli (Frontiers in Microbiology, 2024)
Background Polymyxin B (PMB) and polymyxin E (colistin, CST) are polymyxin antibiotics, which are considered last-line therapeutic options against multidrug-resistant Gram-negative bacteria in serious infections. However, there is increasing risk of resistance to antimicrobial drugs. Effective efflux pump inhibitors (EPIs) should be developed to help combat efflux pump-mediated antibiotic resistance. Methods Chryseobacterium sp. PL22-22A was isolated from aquaculture sewage under selection with 8 mg/L PMB, and then its genome was sequenced using Oxford Nanopore and BGISEQ-500 platforms. Cpr (Chryseobacterium Polymyxins Resistance) genes encoding a major facilitator superfamily-type tripartite efflux system, were found in the genome. These genes, and the gene encoding a truncation mutant of CprB from which sequence called CprBc was deleted, were amplified and expressed/co-expressed in Escherichia coli DH5α. Minimum inhibitory concentrations (MICs) of polymyxins toward the various E. coli heterologous expression strains were tested in the presence of 2–128 mg/L PMB or CST. The pumping activity of CprABC was assessed via structural modeling using Discovery Studio 2.0 software. Moreover, the influence on MICs of baicalin, a novel MFS EPI, was determined, and the effect was analyzed based on homology modeling. Results Multidrug-resistant bacterial strain Chryseobacterium sp. PL22-22A was isolated in this work; it has notable resistance to polymyxin, with MICs for PMB and CST of 96 and 128 mg/L, respectively. A novel MFS-type tripartite efflux system, named CprABC, was identified in the genome of Chryseobacterium sp. PL22-22A. Heterologous expression and EPI assays indicated that the CprABC system is responsible for the polymyxin resistance of Chryseobacterium sp. PL22-22A. Structural modeling suggested that this efflux system provides a continuous conduit that runs from the CprB funnel through the CprC porin domain to pump polymyxins out of the cell. A specific C-terminal α-helix, CprBc, has an activation function on polymyxin excretion by CprB. The flavonoid compound baicalin was found to affect the allostery of CprB and/or obstruct the substrate conduit, and thus to inhibit extracellular polymyxin transport by CprABC. Conclusion Novel MFS-type tripartite efflux system CprABC in Chryseobacterium sp. PL22-22A mediates resistance to polymyxins, and baicalin is a promising EPI.